THE INFLUENCE OF BRANDS, PROMOTION AND ONLINE MARKETING ON THE LOYALTY OF AFIFATHIN GAMIS CONSUMERS IN SIDOARJO - Enny Istanti; Bramastyo Kusumo Negoro (ITB AAS Indonesia Surakarta, 2021)
The era of globalization of the business world in Indonesia is growing very rapidly, this is due to the existence of several economic policies that are being launched by the government in the form of deregulation and debureaucracy. Qualitative research methods using SPSS. The population used is 950 and samples taken are 90 respondents using the Slovin formula. The variables in this study consist of independent variables, namely brand, promotion and online marketing, while the dependent variable is consumer loyalty. To determine the effect simultaneously and partially, multiple linear regression analysis is used. The conclusion of this research is that there is a simultaneous and partial influence of brand, promotion and online marketing on consumer loyalty of gamis afifathin. The dominant variable affecting consumer loyalty is brand. Keywords: Brand, Promotion, Online Marketing and Consumer Loyalty.